Islamic Religious Education Learning During the Covid-19 Pandemic in Lampung Province - Syafe’i, Imam; Yusnita, Erni; Anshori, Irfan (CV. Creative Tugu Pena, 2023)
The Covid-19 pandemic has succeeded in changing the entire structure of world society. Many sectors have been affected by the ferocious spread of the Covid-19 virus; economic, tourism and even education sectors. The aim of this research is to describe Islamic Religious Education learning patterns in Lampung province which took place during the Covid-19 pandemic era. This type of research is qualitative. The research was conducted in Lampung Province targeting all educational institutions starting from primary, secondary and upper education levels. The data sources in this research were obtained from interviews; Interviews were conducted with teaching staff, education staff, students and students' parents. The research results illustrate that the Islamic Religious Education learning process in the Covid-19 pandemic era in Lampung Province encountered many obstacles. The use of online learning platforms such as Google Classroom, Google Meet, Zoom Meeting is not evenly distributed. To support the use of online learning applications, an internet quota is also required which then becomes an unexpected expense for all students' parents; and is considered a drain on your wallet. Use device for each student whose ownership is not evenly distributed due to diverse economic backgrounds. Uneven internet networks and limited teaching are also factors that policy makers need to pay attention to. Learning methods or strategies, especially Islamic Religious Education in Lampung Province, have been changed to use online learning platforms. The curriculum used in the pandemic era in Lampung Province uses an emergency curriculum. Keywords: Islamic Religious Education, Pandemic Learning, Covid-19